2015
DOI: 10.1111/jnp.12078
|View full text |Cite
|
Sign up to set email alerts
|

Improving left spatial neglect through music scale playing

Abstract: The study assessed whether the auditory reference provided by a music scale could improve spatial exploration of a standard musical instrument keyboard in right-brain-damaged patients with left spatial neglect. As performing music scales involves the production of predictable successive pitches, the expectation of the subsequent note may facilitate patients to explore a larger extension of space in the left affected side, during the production of music scales from right to left. Eleven right-brain-damaged stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
2
15
0
2
Order By: Relevance
“…Besides motricity, music-based interventions have also been investigated for effects on cognitive functions. Some examples are symptoms of spatial (41), unilateral (42)(43)(44) and visual neglect (45,46), memory in Alzheimer subjects (47), verbal memory and learning in Alzheimer subjects (48,49) and MS subjects (50,51). These studies showed improvements in the cognitive outcomes measured.…”
Section: The Effectiveness Of Interventions In the Context Of Music-based Interventions Hasmentioning
confidence: 95%
“…Besides motricity, music-based interventions have also been investigated for effects on cognitive functions. Some examples are symptoms of spatial (41), unilateral (42)(43)(44) and visual neglect (45,46), memory in Alzheimer subjects (47), verbal memory and learning in Alzheimer subjects (48,49) and MS subjects (50,51). These studies showed improvements in the cognitive outcomes measured.…”
Section: The Effectiveness Of Interventions In the Context Of Music-based Interventions Hasmentioning
confidence: 95%
“…Bodak et al (22) examined the effectiveness of MNT using musical instruments, chime bars, which were aligned horizontally extending into the neglect visual field. Bernardi et al (23) used playing a music scale on the keyboard with decreasing range into the neglect field. Both studies tried to exercise perceptual-attentional and motor-intentional deficits by asking subjects to complete musical patterns whose lengths was increasingly extended into the visual neglect field.…”
Section: Introductionmentioning
confidence: 99%
“…Dando enfoque às intervenções que constituem os programas de reabilitação estudados nos artigos primários supracitados, verifica-se que a estimulação auditiva e rítmica foi a mais utilizada [17,18,21,23,26], seguindo-se da terapia com suporte musical [16,18,19,27], a terapia de entonação melódica [21] e a musicoterapia [25]. Nas duas revisões foram incluídos estudos primários com intervenção da musicoterapia, terapia de entonação melódica, terapia com suporte musical e estimulação auditiva rítmica.…”
Section: Tabela II -Sumarização Dos Estudos Incluídos Na Revisão (Ver Pdf Em Anexo)unclassified
“…O intervalo de tempo de implementação dos programas variou entre 8 e 18 semanas, com sessões entre 2 e 3 vezes por semana, em que cada uma poderia durar entre 20 minutos e 1 hora. Os resultados obtidos não são todos consensuais, no entanto são descritos ganhos nas habilidades motoras, cognitivas, melhorias na comunicação e no desempenho das Atividades de Vida Diárias (AVDs) [16,19,20,27].…”
Section: Tabela II -Sumarização Dos Estudos Incluídos Na Revisão (Ver Pdf Em Anexo)unclassified